Komodifikasi Tradisi Omed-Omedan Banjar Kaja Desa Adat Sesetan Kota Denpasar - Saskita, I Nyoman Urip Satyaraga Arya; Arjawa, I Gst. Pt. Bagus Suka; Kamajaya, Gede (Lenggogeni Data Publishing, 2024)
This study aims to provide a comprehensive overview of the commodification process based on community initiatives, accompanied by complete information regarding the timeline and involvement of the actors. The form of commodification in this tradition is packaged in the form of a festival and the addition of cultural attractions and